2014
DOI: 10.1111/adb.12174
|View full text |Cite
|
Sign up to set email alerts
|

Chronic loss of noradrenergic tone produces β‐arrestin2‐mediated cocaine hypersensitivity and alters cellular D2 responses in the nucleus accumbens

Abstract: Cocaine blocks plasma membrane monoamine transporters and increases extracellular levels of dopamine (DA), norepinephrine (NE), and serotonin (5-HT). The addictive properties of cocaine are mediated primarily by DA, while NE and 5-HT play modulatory roles. Chronic inhibition of dopamine β-hydroxylase (DBH), which converts dopamine (DA) to norepinephrine (NE), increases the aversive effects of cocaine and reduces cocaine use in humans, and produces behavioral hypersensitivity to cocaine and D2 agonism in rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Mice that lack dopamine b-hydroxylase (Dbh2/2 mice) cannot synthesize norepinephrine and are hypersensitive to cocaine. Interestingly, these animals had reduced barr2 in the nucleus accumbens and altered D2 receptor function (Gaval-Cruz et al, 2016). Overexpressing barr2 in the nucleus accumbens of Dbh2/2 mice reversed the cocaine hypersensitivity (Gaval-Cruz et al, 2016), demonstrating the complex effects that barr2 can have in cocaine-induced locomotion.…”
Section: B-arrestin 2 and Drug Addictionmentioning
confidence: 97%
“…Mice that lack dopamine b-hydroxylase (Dbh2/2 mice) cannot synthesize norepinephrine and are hypersensitive to cocaine. Interestingly, these animals had reduced barr2 in the nucleus accumbens and altered D2 receptor function (Gaval-Cruz et al, 2016). Overexpressing barr2 in the nucleus accumbens of Dbh2/2 mice reversed the cocaine hypersensitivity (Gaval-Cruz et al, 2016), demonstrating the complex effects that barr2 can have in cocaine-induced locomotion.…”
Section: B-arrestin 2 and Drug Addictionmentioning
confidence: 97%
“…D2R activation in iMSNs produces well-described changes in intracellular signaling, biochemical pathway and gene expression (Girault and Greengard, 2004; Tritsch and Sabatini, 2012; Walker et al, 2015). The electrophysiological consequences of D2R activation, however, are still controversial (Gaval-Cruz et al, 2014; Hernandez-Lopez et al, 2000; Lemos et al, under review; Nicola et al, 1996) in part because MSNs lack the G-protein inward-rectifying potassium (GIRK) channels that are responsible for generating the D2R-mediated currents in other neurons such as midbrain DA neurons (Beckstead et al, 2004). Adding to the complexity is the diverse expression pattern of D2Rs in the striatum, which has limited the interpretation of experiments relying on pharmacology to characterize the effect of D2R activation in iMSNs because D2Rs are also expressed in cholinergic interneurons (Maurice et al, 2004; Zhang et al, 2009), and in presynaptic terminals from midbrain DA neurons (Adrover et al, 2014; Ford, 2014) and corticostriatal glutamatergic neurons (Bamford et al, 2004a; Bamford et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms that lead to DA-induced changes in cellular excitability are complex. Some have reported that the D2/D3 agonist quinpirole has no effect on excitability (Lemos, Friend, Kaplan et al, 2016), while others have reported that quinpirole causes a decrease in intrinsic excitability (Gaval-Cruz, Goertz, Puttick et al, 2014;Urs, Gee, Pack et al, 2016). While the D2 cell response is largely dose-dependent, D1 agonists can facilitate either an increase or decrease in firing rate depending on the resting membrane potential (Hernández-López, Bargas, Surmeier et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in βarr2 in the NAc affect cocaine-induced locomotion (Gaval-Cruz, Goertz, Puttick et al, 2014). Although the modulation of drug responses by barr2 are thought to occur within mesolimbic circuitry, the striatal cell-types have not been fully identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation